DETERMINANTS OF RURAL WOMEN POULTRY FARMERS’ ACCESS TO AGRICULTURAL INFORMATION IN IMO STATE, NIGERIA: A LOGIT MODEL ANALYSIS - F.C, Anaeto; D.O, Ohajianya; A.O, Ani; A.O, Ani A.O; Njoku E.C, Mathews; O.C, Korie; U.C, Ozor; Nnebene E, Adolph; C.O, Osuagwu (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2017)
The study analyzed the determinants of rural women poultry farmers’ access toagricultural information in Imo State, Nigeria. Data were obtained in 2015 with structured and validated questionnaire from 201 proportionately and randomlyselected rural women poultry farmers. Data were analyzed using descriptive statistics (mean and percentage) and inferential statistics (logit model). Resultsshowed that extension contacts, attendance to agricultural extension seminars and workshops, as well as accessibility of media methods were very poor.Determinants, of rural women poultry farmers’ access to agricultural information were age, education level, frequency of attendance to associations’meetings, farming experience, farm size, attendance to agricultural extension seminars and workshops, access to credit, and accessibility to media methods.Rural women poultry farmers should be encouraged to participate actively in extension services organized trainings, seminars and workshops to improvetheir access to agricultural information